The Discourse of History Writing: Mochtar Lubis' Social Criticism of Campus and Students through "Tadjuk Rentjana" Harian Indonesia Raya (HIR) in the Early New Order Period - Febbrizal, Febbrizal; Abdurakhman, Abdurakhman (Jurnal Sejarah Indonesia, 2024)
This article examines the discourse of writing press history with a focus on Mochtar Lubis's social criticism of campuses and students. The discourse of writing the history of the press is sourced from the "tadjuk rentjana" of Harian Indonesia Raya written by Mochtar Lubis during the early span of the New Order in 1968-1974. This naturally gives rise to the question of how editorial plans that became the face of a press institution such as Harian Indonesia Raya became a medium for Mochtar Lubis to conduct social criticism. The methodology employed is a literature review and content analysis of pertinent sources. The initial section of this article delineates Mochtar Lubis' social and intellectual background. The subsequent section examines Mochtar Lubis' social criticism as manifested in HIR editorials. The concluding section elucidates the discourse surrounding the writing of his history.